Peran Jintan Hitam (Nigella sativa) Sebagai Pengobatan Diabetes Mellitus - Intan Nanda Rezeki (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Diabetes mellitus (DM) is a disease characterized by an increase in glucose in the blood (hyperglycemia) and occurs when the pancreas does not produce insulin or when the body cannot effectively use insulin. The results of Indonesia Basic Health Research in 2018, showed the prevalence of DM in Indonesia increased and almost each province has increased. This is caused by unchanging risk factors such as sex, age, and genetic factors, the second is risk factors that can be changed such as smoking habits, education level, occupation, physical activity, smoking habits, alcohol consumption, body mass index, waist circumference and age. This disease is called the silent killer because it can affect all organs of the body and cause various kinds of complication. Management of it uses the four pillars such as educational management, lifestyle modification, exercise and the use of anti-diabetes drugs. However, herbal medicine is currently being developed to help overcome this degenerative disease in order to reduce the prevalence with using black cumin or Nigella Sativa. Black cumin is a plant that is high in fiber with a low glycemic index and contains high nutritional value including monosaccharides, rhamnose, xylose, arabinose, and non-starch polysaccharides. Black cumin can be processed into powder, extract or oil. Antidiabetic mechanisms of cumin seeds through the protective effect of beta cells on oxidative stress, induction of cell-â proliferation, reducing MDA levels in pancreatic tissue, decreasing plasma levels of the hormone leptin, increasing Glut-4 expression and decreasing gluconeogenesis in the liver.